Digital cranial endocast of Riograndia guaibensis (Late Triassic, Brazil) sheds light on the evolution of the brain in non-mammalian cynodonts. (21st October 2019) - Rodrigues, Pablo Gusmão; Martinelli, Agustín G.; Schultz, Cesar Leandro; Corfe, Ian J.; Gill, Pamela G.; Soares, Marina B.; Rayfield, Emily J.
Abstract: A digital cranial endocast of the specimen UFRGS-PV-596-T of Riograndia guaibensis was obtained from μCT scan images. This is a small cynodont, closely related to mammaliaforms, from the Late Triassic of Brazil. Riograndia has large olfactory bulb casts and the cerebral hemispheres region is relatively wider than in other non-mammaliaform cynodonts. Impressions of vessels were observed and a conspicuous mark on the dorsal surface was interpreted as the transverse sinus. The calculated encephalization quotient is greater than the range seen in most other non-mammaliaform cynodonts. The ratios between linear and area measurements of the dorsal surface suggest four evolutionary changes from a basal eucynodont morphology to mammaliaforms, involving an evolutionary increase of the relative size of the olfactory bulbs and the width of the cerebral hemispheres and cerebellum. The data supports the hypothesis of the neurological evolution of the mammalian lineage starting with a trend for an increase of the olfactory bulbs, which is associated with adaptations in the nasal cavity. This trend is suggested to be linked to the selective pressures for small-sized faunivorous, and probably nocturnal, animals, and represents an initial improvement of the sensory receptor system, subsequently leading to further development of the 'superior' structures for sensorial processing and integration.